2022
DOI: 10.1111/ijac.14163
|View full text |Cite
|
Sign up to set email alerts
|

Effects of nitridation temperature on properties of sintered reaction‐bonded silicon nitride

Abstract: We prepared sintered reaction-bonded silicon nitride ceramics by using yttria and magnesia as sintering additives and evaluated effects of the nitridation temperature on their microstructure, bending strength, fracture toughness, and thermal conductivity. The effects of the nitridation temperature were large, but different depending on the property. The ratio of β-phase in the nitrided compacts significantly increased with increasing the nitridation temperature, whereas their microstructures had no clear diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…40) Suppose the compositions and post-sintering conditions are the same, the lattice oxygen amounts can be roughly evaluated by the ¢ ratio of the nitrided compacts, and the higher value indicates the lower oxygen contents. 28) In this work, the microstructural characteristics were the dominant factor for the thermal conductivity rather than the oxygen contents, and the heating rate of 8 °C/min, which has the higher density and the greater number of the large grains, showed the highest thermal conductivity, as shown in Table 1.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…40) Suppose the compositions and post-sintering conditions are the same, the lattice oxygen amounts can be roughly evaluated by the ¢ ratio of the nitrided compacts, and the higher value indicates the lower oxygen contents. 28) In this work, the microstructural characteristics were the dominant factor for the thermal conductivity rather than the oxygen contents, and the heating rate of 8 °C/min, which has the higher density and the greater number of the large grains, showed the highest thermal conductivity, as shown in Table 1.…”
Section: Discussionmentioning
confidence: 73%
“…17) Zhou et al 18) prepared the Si 3 N 4 ceramics with the addition of 2 mol.% Y 2 O 3 and 5 mol.% MgO, which achieved the highest thermal conductivity ever reported of 177 W/(m•K) and better fracture toughness of 11.2 MPa m 1/2 by the SRBSN method. The features of reactant Si particles, 19)23) post-sintering condition, 18),24)27) and nitridation temperature 28) at this composition have been investigated. However, to the best of our knowledge, there have been no studies investigating the effect of heating rate during the nitridation procedure.…”
Section: Introductionmentioning
confidence: 99%
“…This increase was due to the reduction of internal F I G U R E 7 Relation between thermal conductivity and bending strength for Si 3 N 4 sintered by different routes. GPS, 14,28,[40][41][42][43][44][45] gas pressure sintered; SRBSN, sintered reaction-bonded silicon nitride 2,16,18,46,47 ; HP, hot pressing [48][49][50] ; SPS, spark plasma sintering 51,52 ; PLS, pressureless sintering 33 ; HPFS, hot-pressing flowing sintering.…”
Section: Thermal Conductivitymentioning
confidence: 99%
“…[8][9][10][11][12][13] It was found that raising the sintering temperature and prolonging the sintering time was adequate for increasing the thermal conductivity, 8 while the strength decreased because of grain growth. 14 In the previous work, 15 we investigated the nitridation temperature for silicon compact and achieved compatibly high mechanical strength and thermal conductivity, which are generally known to be in a trade-off relationship. This is because the microstructures and characteristics of the sintered body are strongly affected by those of the nitrided one.…”
Section: Introductionmentioning
confidence: 99%